Bioinspired Ultrastrong Nanocomposite Membranes for Salinity Gradient Energy Harvesting from Organic Solutions - Chen, Cheng; Liu, Dan; Yang, Guoliang; Wang, Jiemin; Wang, Lifeng; Lei, Weiwei (Advanced energy materials, 2020)
Efforts to extract energy from waste organic solutions can not only support clean environments but also help to alleviate the energy crisis. Here, a bioinspired ultrastrong nanocomposite membrane is developed via the layer‐by‐layer method based on aramid nanofiber‐graphene oxide (AGO) with good mechanical properties for salinity gradient energy harvesting from organic solutions. Benefiting from the 1D and 2D network interlocking arrangement, the AGO membrane shows an unprecedented mechanical stress of 688 MPa and maintains its integrity after soaking in organic solvents for 24 h. Impressively, when LiCl is diluted in methanol, the AGO membrane device with a working area of 113 mm2 produces a current and a measured power generation of 28 ± 11 µA and 3140 ± 960 nW (Cfeed = 2 mol L−1), respectively. Thus, the working area of the AGO membrane for salinity gradient energy harvesting and temperature‐related energy harvesting enables its use in practical applications. In addition, 14 cells with the methanol‐LiCl solution (Cfeed = 1 mol L−1) can produce a voltage up to 1.82 V to light a liquid crystal display. Therefore, this AGO nanocomposite membrane presents a promising avenue to harvest salinity gradient energy from organic solutions. Bioinspired ultrastrong aramid nanofiber‐graphene oxide (AGO) nanocomposite membranes are developed by the layer‐by‐layer method based on aramid nanofibers and graphene oxide nanosheets. The AGO membrane shows an unprecedented mechanical stress of 688 MPa and a promising avenue to harvest salinity gradient energy from organic solutions.